Residual toxicities of synergized pyrethrins and methoprene applied as aerosol insecticides - Sutton, April E. (Kansas State University, 2009)
Tribolium spp. are major pests in structures used for the processing and storage of grain-based products (e.g., flourmills, warehouses, retail stores). Consumers and regulators have little tolerance for insect-damaged or contaminated food products. The direction and breadth of pest-control strategies in the food industry have changed significantly over the past few years, creating the need to optimize insecticides through improved integrated pest management (IPM) techniques, specifically through the identification of new control agents that are low in mammalian toxicity, as well as any factors that might affect susceptibility to these agents. There is currently renewed interest in developing reduced-risk, low toxicity chemicals that can be effectively utilized in a setting in which grain and other food commodities are vulnerable to insect infestation, as a means of replacing outdated, and at times, less effective methods of insect control. Over the past decade, developed countries have made significant progress toward alternative insect control strategies by employing a variety of applied insecticides. Two classes of insecticide include natural pyrethrum and insect growth regulators (IGRs), which are substances that mimic insect hormones essential to normal development and reproduction. Pyrethrin is a highly efficient, broad spectrum, botanical insecticide that causes a rapid knockdown in exposed insects. Synergists are used to extend the economic usage of natural pyrethrins and because pyrethrum is rapidly metabolized, it is often mixed with a synergist. Methoprene, a juvenile hormone analog, is labeled as an aerosol and surface treatment inside mills, warehouses and other food storage facilities. There is little recent research with large-scale aerosol applications in stored-food facilities; furthermore, there are few published references regarding the efficacy of using methoprene in combination with synergized pyrethrin, in aerosol form. Therefore, the purpose of this research was to evaluate the use of aerosol applications of two aerosol concentrations on flour and finished stored-product packaging materials for the control of Tribolium spp. Results of this research show that T. castaneum are effectively controlled with 1% aerosol application, while the 3% formulation is required to effectively control T. confusum. With regards to the various packaging material surfaces, few differences between the surfaces emerged.
Keywords: pyrethrin; methoprene; aerosol; insecticide; Tribolium spp.; stored products; Biology, Entomology (0353)